INTEGRATION OF THE LATEST METHODS BASED ON SCAFFOLDING TECHNOLOGY IN THE PROCESS OF DEVELOPING TRANSLATORS’ SOFT SKILLS - Svitlana Amelina; Rostyslav Tarasenko; Hongming Wang (Alfred Nobel University Journal of Pedagogy and Psychology, 2025)
The article deals with the problem of developing soft skills in prospective translators in the process of their vocational training in higher education institutions. The purpose of the article is to identify opportunities for integrating the latest methods based on scaffolding technology in the process of training prospective translators to develop their soft skills. To achieve the stated purpose, a set of methods was used: the method of analysis and synthesis to study regulatory documents and publications of scientists on the subject of the study; the method of pedagogical experiment to clarify the possibilities of using the latest methods to form soft skills in prospective translators with their integration with scaffolding technology; the method of generalization to formulate the conclusions of the study. It has been found that in the modern market of translation services, employers focus not only on the formation of translators’ professionally significant competencies, but increasingly also on their soft skills. Based on the analysis of employers’ requirements, soft skills important for translation activities have been identified. These include initiative, leadership, communication skills, teamwork, time management, and emotional intelligence. It is taken into account that the rapid development of information technologies in the field of translation has led to the emergence of new forms of organizing the work of translators, in par- ticular, in the form of the implementation of translation projects by a group of performers. An experimental study was conducted on the formation of certain soft skills through the use of scaf- folding technology in combination with the project method and the modelling method during the study of the course “Information Technologies in Translation Projects”. Attention is focused on the gradual decrease in teacher support provided to participants in educational translation projects at various stages of their im- plementation. When adapting the project method to the research goal, the following stages were identi- fied: determining the leader, forming a team, assigning roles, defining tasks, performing tasks, finalizing the work, analysing and discussing the results. It was found that the fullest possible use of the potential of each stage for the formation of certain soft skills is possible by synchronizing the stages determined by the project method with the stages of the simulated process of implementing translation projects. During the experiment, the Phrase TMS cloud-based automated translation system was used as a specialized tool for performing translation tasks. Based on the questionnaire, the state of students’ awareness of the importance of forming soft skills, significant for the activity of a translator, and their self-assessment of their formation were clarified. Those aspects of forming soft skills at the stages of implementing translation projects that require maximum sup- port from the teacher were identified. These were initiative and teamwork. The conclusions confirmed the feasibility of integrating such methods as the project method and modelling with scaffolding technology, which contributed to the effectiveness of the process of forming soft skills in prospective translators.